2007
DOI: 10.1590/s1519-566x2007000400021
|View full text |Cite
|
Sign up to set email alerts
|

Miasis humana en Bahía Blanca, Argentina: periodo 2000 / 2005

Abstract: -Myiasis is the infestation of live human and vertebrate animals with dipterous larvae which, at least for a short period, feed on the host's dead or living tissue, liquid body-substance, or ingested food. The objective of this study was to identify the flies producing myiasis in Bahía Blanca city, Argentina, from 01/03/2000 to 31/05/2005. Seventeen clinical cases were studied. The larvae obtained from lesions were forwarded from laboratories and from public and private hospitals. Part of the larvae were fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…However according to Marquez et al (2007), the higher occurrence of myiasis was among men, a fact also observed by Visciarelli et al (2007) who also described that 76.5% of the cases took place during the summer corroborating the results of this research when the percentage of parasitized males was 54.5%, and emphasizing that most of these men were employed in construction, farming, or domestic activities (75%). Such activities promote greater contact with the flies that cause myiasis.…”
Section: Discussionsupporting
confidence: 87%
“…However according to Marquez et al (2007), the higher occurrence of myiasis was among men, a fact also observed by Visciarelli et al (2007) who also described that 76.5% of the cases took place during the summer corroborating the results of this research when the percentage of parasitized males was 54.5%, and emphasizing that most of these men were employed in construction, farming, or domestic activities (75%). Such activities promote greater contact with the flies that cause myiasis.…”
Section: Discussionsupporting
confidence: 87%
“…Visciarelli et al [17] have cited the species incriminated in human myiasis, C. hominivorax and Phaenicia sericata (also called Lucilia sericata ) (Meigen), to Bahia Blanca, Buenos Aires, Argentina. In all patients, myiasis occurred after traumas, lesions, and/or infectious processes that attracted the flies.…”
Section: Discussionmentioning
confidence: 99%
“…Visciarelli et al [17] also mentioned different pathologies, such as diabetes, otitis, and alcoholism, and certain behaviors, such as lack of body hygiene, lack of personal grooming, and/or rural tasks, that favour the permanence of the wounds by causing insensibility and increasing the probability of contact with flies. In the present work, we agree with the hypothesis that the exposed ulcer was a conditioning factor that, in combination with the patient's poor personal hygiene, rural tasks and insensibility associated with diabetes determined the degree of evolution of the myiasis in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Cochliomyia hominivorax and Chrysomya bezziana are cause dangerous myiasis due to their painful infestation and deep invasion (4). Wohlfahrtia magnifica (13), Dermatobia hominis (14), Lucilia cuprina (4) and L. sericata (15) are known to be causative agent for wound myiasis . Therefore, L. sericata and L. cuprina should be distinguished from each other as the presence of the three bristles on the dorsal mesothorax is considered the most common characteristic of L. sericata.…”
Section: Discussionmentioning
confidence: 99%